Numerical Investigation of Defect Severity in Double-Slope 16MnR Steel Cracked Pipes with Uniform Corrosion Using the XFEM-Level Set Method - Salmi, Houda; Lifi, Houda; EL Had, Khalid; Hachim, Abdelilah; Lamati, Amal (International Journal of Integrated Engineering, 2026)
This study presents a numerical investigation into the severity of semi-elliptical surface cracks in 16MnR steel pipes featuring double-slope thickness transitions and subjected to uniform corrosion under internal pressure. The analysis employs a coupled XFEM–Level Set approach integrated with a Fick-based corrosion model, implemented in the CASTEM platform using a mesh comprising 9,290 CUB8 elements and 200 enriched XC8R elements to accurately capture stress singularities near crack fronts. Model validation against ASME B31G analytical solutions confirms high fidelity, with deviations below 5% across crack depth-to-thickness ratios (a/t) from 0.1 to 0.8 and aspect ratios (a/c) ranging from 0.125 to 1. Simulations were conducted under representative industrial operating pressure. Results indicate that the primary thickness transition ratio (t₁/t) critically governs stress concentration: increasing t₁/t from 1.5 to 6 raises the stress intensity factor (K) at the deepest crack point from 20.4 to 105.9 MPa√m—surpassing the critical fracture toughness of 16MnR steel (90 MPa√m) and inducing localized plasticity. Conversely, as cumulative metal loss (t_c) rises from 0% to 60%, K decreases from 14.6 to 9.5 MPa√m due to crack tip blunting. These findings highlight that initial geometric discontinuity—not secondary corrosion-induced thinning—is the dominant factor controlling defect severity. The study thus offers a robust quantitative basis for structural integrity assessment and residual life prediction in corroded pressurized pipelines.